Customer's Decision to Open a Bank Account Using Mobile Banking Application: Case In The Muamalat Digital Islamic Network (MDIN) - Muliansyah, Ainol; Mubarok, Arif; Arifin, Muhammad Zainal; Monady, Hanief (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2024)
As digital technology based on the Internet of Things (IOT) develops, it should be able to increase banking access (inclusivity) for customers and attract the interest of potential customers. Banking digitalization is currently much more developed than just transaction features but also includes a savings account opening system. Bank Muamalat Indonesia is one of the sharia banks that participates in the development of digital technology by presenting a mobile banking application called MDIN or Muamalat Digital Islamic Network. Digitalization of sharia banking should provide convenience and attract the interest of potential customers, considering that the market share of sharia financial institutions in Indonesia is still low. This research aims to determine customer preferences for opening a savings account via MDIN. This research uses a qualitative research method with a case study approach. The objects of research include customer preferences in using MDIN digital banking. The subjects of this research are customers who open savings accounts through MDIN. The research results show that customer preferences in using MDIN as an option for opening a savings account are based on several factors such as social factors, ease of service, benefits and personal factors. Social and personal factors are the most dominant factors in customer’ decision making to open a savings account through MDIN digital banking.